Analisis Penerapan Etos Kerja Islam pada Pegawai Kantor Urusan Agama Tapen, Kabupaten Bondowoso, Jawa Timur - Muhammad Saliki Robi; Ahmad Zaidan Mufid; Muhammad Hilman Firmansyah; Aniqotuzzuhro’ Fitriana (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2023)
This article aims to find out the application of the Islamic work ethic to employees of the Tapen Regency Religious Affairs Office. This study uses a qualitative descriptive research technique. Data collection methods used are interviews, observation and documentation. Data analysis in this study used triangulation techniques. The results of this study indicate that the KUA staff of Tapen Regency have started to apply an Islamic work ethic by carrying out work based on the Al-Quran and Hadith by applying sincerity, honesty, consistency, courage to accept consequences, and responsibility. The Islamic work ethic applied by employees has a visible impact from increasing employee performance and satisfaction with the services provided by employees of the Office of Religious Affairs.